CementalTear Predisposing Factors, Clinical Signs Symptoms, Diagnosis and its Management - Shama Asghar (Journal of Bahria University Medical and Dental College)
A cemental tear is a rare condition in which a total or partial detachment of the cementum occurs along the root surfaceat the cemento-dentinal junction and is associated with moderate to severe periodontal attachment loss. Literature regarding this article was searched fromPub Med, Medline and Google during the period of Jan 2008- Dec 2012.Cemento-dentinal tear is more frequently seen in older men above 60 years, single-rooted vital or nonvital teeth, particularly the incisors and premolars areinvolved. Other significant etiological factors are traumatic occlusion, poor ability of tissue healing due to age and structural weakness of the cementum. Its diagnosis can be confirmed by clinical signs and symptoms,(presence of localized periodontal pockets with exudates and localized pain) by radiographic findings(as a radiopaque fragment) and surgical inspection. The treatment of cemental tears involves scaling and root planning, open flap debridement, bone graft, regenerative tissue guide, apical surgery and dental extraction